2012
DOI: 10.1088/0954-3899/39/11/115001
|View full text |Cite
|
Sign up to set email alerts
|

Easy as πo: on the interpretation of recent electroproduction results

Abstract: Our original suggestion to investigate exclusive π o electroproduction as a method for extracting from data the tensor charge, transversity, and other quantities related to chiral odd generalized parton distributions is further examined. We now explain the details of the process: i) the connection between the helicity description and the cartesian basis; ii) the dependence on the momentum transfer squared, Q 2 , and iii) the angular momentum, parity, and charge conjugation constraints (J P C quantum numbers).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(102 citation statements)
references
References 26 publications
5
97
0
Order By: Relevance
“…It was recently suggested to use dispersion relations in order to relate the real and imaginary parts of CFFs. However, as we noted in [11], dispersion relations do not apply straightforwardly because of the appearance of tdependent physical thresholds. As a result, we reiterate that both the real and imaginary parts need to be extracted separately from experiment, at variance with the simplification suggested e.g.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was recently suggested to use dispersion relations in order to relate the real and imaginary parts of CFFs. However, as we noted in [11], dispersion relations do not apply straightforwardly because of the appearance of tdependent physical thresholds. As a result, we reiterate that both the real and imaginary parts need to be extracted separately from experiment, at variance with the simplification suggested e.g.…”
Section: Introductionmentioning
confidence: 91%
“…In Ref. [19] we in fact pointed out that the ERBL region, or the region with X < ζ, cannot be described in terms of a quark anti-quark pair emerging from the nucleon because of the presence of semi-disconnected, unphysical, diagrams associated to this configuration (Fig.1b). While casting a doubt on any partonic picture in the ERBL region, we also suggested that multi-parton distributions may restore the connectedness, and consequently the partonic interpretation of the DVCS graphs.…”
Section: Introductionmentioning
confidence: 99%
“…There are seven conserved independent form factors, G i (t), i = 1, 7, and an additional non conserved term, g µν ( * )M 2 G 8 (t). In analogy with the nucleon case [10,11], the enumeration of the independent deuteron EMT form factors, as well its Lorentz structure, was obtained using the partial wave formalism and crossing symmetry (details on our method for counting the form factors are presented in [12] (nucleon) and in an upcoming paper [13] (deuteron)). The energy momentum tensor was constructed by considering all independent scalar, vector, axial-vector, and tensor components formed with the polarization and momentum four-vectors.…”
mentioning
confidence: 99%
“…The theoretical description of these processes is more complicated, and thus measurements that provide information about the reaction mechanism, e.g., tests of hard-soft factorization, are essential. In particular, the emerging transversity GPDs [114][115][116] may be accessed if dominance of the transverse cross section at small values of t <0.3 GeV 2 can be experimentally verified.…”
Section: D Spatial Mapping -Gpdsmentioning
confidence: 99%